Research on the Effect of IIDG on Local Feeder Protection - Jingsong DENG; Yingmin WANG; Difei SUN; Chenling ZHENG; Hanting YAN; Xiaojing GAO (发电技术)
Because of its outstanding performance in economic benefit and environmental benefit, the inverter interfaced distributed generation (IIDG) has been widely used in distribution network. The access of IIDG makes the distribution network a complex network of multi-power supply, the bidirectional power flow may lead to the degradation of feeder automation performance based on undirectional power flow, and it is imposssible to isolate faults in time. Aiming at two typical application on overhead lines feeder automation implementation pattern: voltage time type feeder automation and current differential type feeder automation, discussed its working principle, considering the working principle of IIDG, the influence of IIDG's penetration on fault isolation and non-faulty area recovery in each feeder automation mode was analyzed in detail. The solution to reduce the impact of IIDG was proposed and the simulation was verified.